Efek Paparan Asap Rokok Terhadap Kadar Total Antioxidant Capacity (TAC) - Zulaikhah, Siti Thomas (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Cigarette smoke caused by smoking is a factor in the risk of lung cancer, respiratory tract infections, and cardiovascular disease. Particles contained in cigarette smoke have the potential to increase the content of free radicals in the body and lower antioxidant levels. Levels of Total Antioxidant Capacity (TAC) reflects the amount of all antioxidants in the body and acts as a biomarker of antioxidant protection against free radicals. The purpose of this study was to investigate the impact of cigarette smoke exposure on TAC levels in wistar strain rats exposed to cigarette smoke. Design used is experimental with posttest only control group design. Independent variable in this research was cigarette smoke exposure and the dependent variable was levels of TAC. The study population is male wistar strain rats adapted in inter university research/ Penelitian Antar Universitas (PAU) Universitas Gajah Mada Yogyakarta Penelitian Antar Universitas (PAU) Universitas Gajah Mada Yogyakarta. Twelve male rats used in the study were randomly divided into 2 groups, group K1 (fed standard food et libitum + aquadest) K2 (fed standard food et libitum + aquadest + cigarette smoke exposure 3 buds/day). Treatments were given for 14 days. Day 15 rats blood are drawn to be checked for TAC using ELISA (Enzyme-Linked Immunosorbent Assay), data were analyzed using Mann Whitney test. Result: Mean Levels of TAC on K1: 1,79Â±0,5 mmol/L and K2: 0,56Â±0,06 mmol/L;. The results of the analysis obtained the p value: 0,003(